Does sex influence age at onset in cranial-cervical and upper limb dystonia?. Issue 2 (1st February 2003) - Defazio, G; Abbruzzese, G; Girlanda, P; Vacca, L; Currà, A; Marchese, R; Martino, D; Masi, G; Majorana, G; Mazzella, L; Livrea, P; Berardelli, A
Abstract : The relation between age at dystonia onset and sex was investigated in 264 patients with cranial-cervical dystonia and 56 patients with upper limb dystonia. In cranial-cervical dystonia, women had a significantly greater age at the onset of dystonia than men. The association was independent of duration of disease and distance of referral, but it was no longer detectable after adjustment for educational level. In upper limb dystonia, men and women did not differ for age at dystonia onset, duration of disease, education level, or distance of referral. A significant inverse association between age at the onset of dystonia and education was observed in both cranial-cervical dystonia and upper limb dystonia series.